Associates of prevalence of depression among urban elderly of Kendujhar district: a study in Odisha, India - Barik, Debasmita; Panda, Bharati (International Journal Of Community Medicine And Public Health, 2021)
Background: There is wide variation in the estimated prevalence of depressive disorder among older in India. The estimated prevalence of depression in India is ranging from 6 to 80% depending on various factors of population studies. The present research is an attempt to assess the factors associated with depression among elderly in urban area. Methods: A descriptive study was carried out among older in urban area of Kendujhar district of Odisha, India with sample size 150 by random sampling method. A pre-structured questionnaire containing socio-demographic data sheet and geriatric depression scale (GDS) was used. Results: The overall depressive symptom among elderly was reported to be 66%. Socio-demographic factors such as 70-75 age group, female sex, illiteracy, low education, widowhood and no personal income were significantly associated with depression (p<0.05), where no significant association existed between depression and family income as well as family type. The results showed high significant association of meditation, yoga and exercise with depression. Activity such as marketing and record keeping were positively associated with depression (p<0.05), where no significant association of depression with gardening, cooking and cleaning (p>0.05). Health problems such as weakness, leg pain, knee pain and medical illnesses such as cataract and tuberculosis were positively associated with depression. The findings show depression was not significantly associated with gardening, cooking, cleaning back pain, shoulder pain, headache and asthma (p>0.05). Conclusions: A majority of participants are having depression (66%). There is need to identify and diagnose the problems of aged in urban area and start treatment earlier as possible.